2016
DOI: 10.1016/s0140-6736(16)31229-6
|View full text |Cite
|
Sign up to set email alerts
|

Parent-mediated social communication therapy for young children with autism (PACT): long-term follow-up of a randomised controlled trial

Abstract: SummaryBackgroundIt is not known whether early intervention can improve long-term autism symptom outcomes. We aimed to follow-up the Preschool Autism Communication Trial (PACT), to investigate whether the PACT intervention had a long-term effect on autism symptoms and continued effects on parent and child social interaction.MethodsPACT was a randomised controlled trial of a parent-mediated social communication intervention for children aged 2–4 years with core autism. Follow-up ascertainment was done at three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
350
0
23

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 410 publications
(385 citation statements)
references
References 27 publications
12
350
0
23
Order By: Relevance
“…This has occurred historically for two counterbalancing reasons: (1) because it is generally believed that ADOS scores are diagnostic and are not sensitive to change once the diagnosis is established, and (2) because training effects have the potential to produce improvements that are artifactual. With regard to the first point, under the right circumstances ADOS scores can be sensitive to change and have recently been used successfully as an outcome measure in a large autism treatment study 47. With regard to the second point, if training effects occurred, they were asymmetric, since improvements were only observed in the suramin treatment group and were not observed in the placebo group (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This has occurred historically for two counterbalancing reasons: (1) because it is generally believed that ADOS scores are diagnostic and are not sensitive to change once the diagnosis is established, and (2) because training effects have the potential to produce improvements that are artifactual. With regard to the first point, under the right circumstances ADOS scores can be sensitive to change and have recently been used successfully as an outcome measure in a large autism treatment study 47. With regard to the second point, if training effects occurred, they were asymmetric, since improvements were only observed in the suramin treatment group and were not observed in the placebo group (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings from a trial of parent-mediated communication-focused therapy failed to find clear evidence of effectiveness at 1 year, 22 but did so at 5 years. 37 We cannot rule out the possibility that there could have been differences in outcomes for children over a longer period. However, a further difference from that study is that the involvement of parents allows for generalisation across situations, and the music therapy as delivered in this trial did not consistently involve parents in a way that transferred skills.…”
Section: Strengths and Weaknesses Of The Study Designmentioning
confidence: 98%
“…35,36 The ADOS was originally developed as a diagnostic tool to assess whether or not children have impairments and unusual behaviours that would indicate ASD. Although some previous studies have used the ADOS to assess the clinical effectiveness of interventions, 22,37,38 concerns have been raised about the suitability of the ADOS to assess changes in the adaptive functioning of children with ASD. 39 Similar limitations apply to the SRS as an outcome measure for measurement of skill development in young children.…”
Section: Strengths and Weaknesses Of The Study Designmentioning
confidence: 99%
“…The authors went on to say that future studies need to examine the long-term effects of these early interventions on affected children's development. The second study, documented in 2016, clearly showed that in a long-term follow-up of a randomised controlled trial on parent-mediated social communication therapy for young children with autism (PACT) study, on children 2 to 4 years old with core autism, the results were the first to show long-term symptom reduction after early intervention in autism spectrum disorder 5 . The data supported the clinical value of the PACT intervention and the outcomes have implications for management of affected children.…”
mentioning
confidence: 99%